Anemia, bilirubin, and cardiovascular autonomic neuropathy in patients with type 2 diabetes. Issue 15 (April 2017) - Chung, Jin Ook; Park, Seon-Young; Cho, Dong Hyeok; Chung, Dong Jin; Chung, Min Young
Abstract : Abstract: To investigate the relationship among anemia, physiological serum bilirubin levels, and cardiovascular autonomic neuropathy (CAN) in subjects with type 2 diabetes. In total, 2230 subjects with type 2 diabetes were evaluated in this cross-sectional study. CAN was diagnosed with a cardiovascular reflex test. The prevalence of anemia was greater in subjects with CAN. In multivariable analysis, the relationship between anemia and CAN remained statistically significant after adjusting for the risk factors (odds ratio [OR] 1.39; 95% confidence interval [CI] 1.07–1.80, P  = .015). Additional adjustment for serum bilirubin concentrations abolished this relationship (OR 1.20, 95% CI 0.91–1.58, P  = .189). Anemia is positively associated with the prevalence of CAN in subjects with type 2 diabetes. In addition, our results suggest that the putative increased CAN risk associated with anemia might be mediated by a correlated decrease in serum bilirubin levels.